Elicitation Effect On The Growth And Biochemical Activities Of Curcuma Mangga Val (Zingiberaceae) In Vitro Plantlets - Abraham, Fariz (2010)
Curcuma mangga aseptic plantlets could be established via double-stage surface sterilization technique. The bud explants derived from the rhizomes were immersed in 70% (v/v) alcohol for ten minutes at the first stage followed by surface-sterilized with 20% (v/v) Clorox® for 20 minutes at the second stage. The established aseptic explants were then cultured on the best proliferation medium, which is the MS medium supplemented with 2 mgL-1 6-benzylaminopurine (BAP) and 0.5 mgL-1 1-naphthaleneacetic acid (NAA). Liquid proliferation medium induced more auxiliary shoots (6.7 ± 0.4 shoots/explant) as compared to gelled proliferation medium (4.6 ± 0.6 shoots/explant).